The role of the cGAS-STING pathway in chronic pulmonary inflammatory diseases - Tian, Mengxiang; Li, Fengyuan; Pei, Haiping; Liu, Xiaoling; Nie, Hongyun (Frontiers in Medicine, 2024)
The innate immune system plays a vital role in the inflammatory process, serving as a crucial mechanism for the body to respond to infection, cellular stress, and tissue damage. The cGAS-STING signaling pathway is pivotal in the onset and progression of various autoimmune diseases and chronic inflammation. By recognizing cytoplasmic DNA, this pathway initiates and regulates inflammation and antiviral responses within the innate immune system. Consequently, the regulation of the cGAS-STING pathway has become a prominent area of interest in the treatment of many diseases. Chronic inflammatory lung diseases, such as chronic obstructive pulmonary disease (COPD), asthma, and pulmonary fibrosis, are characterized by persistent or recurrent lung inflammation and tissue damage, leading to diminished respiratory function. This paper explores the mechanism of action of the cGAS-STING signaling pathway in these diseases, examines the development of STING inhibitors and nanomaterial applications, and discusses the potential clinical application prospects of targeting the cGAS-STING pathway in chronic inflammatory lung diseases.